Mental Health and Service Use of Migrants in Contact with the Public Psychiatry System in Paris - Tortelli, Andrea (Int J Environ Res Public Health, 2020)
Background: Migrants, and particularly asylum seekers, are at increased risk of psychiatric disorders in comparison with natives. At the same time, inequalities in access to mental health care are observed. Methods: In order to evaluate whether the Parisian public psychiatric system is optimally structured to meet the needs of this population, we examined data on mental health and service use considering three different levels: the global system treatment level, a psychiatric reception center, and mobile teams specializing in access to psychiatric care for asylum seekers. Results: We found higher treatment rates among migrants than among natives (p < 0.001) but inequalities in pathways to care: more mandatory admissions (OR = 1.36, 95% CI: 1.02–1.80) and fewer specialized consultations (OR = 0.56, 95% CI: 0.38–0.81). We observed a mismatch between increased need and provision of care among migrants without stable housing or seeking asylum. Conclusions: Inequalities in the provision of care for migrants are observed in the Parisian public psychiatric system, particularly for those experiencing poor social and economic conditions. There is a need to facilitate access to mental health care and develop more tailored interventions to reduce discontinuity of care.